PERANCANGAN COVER DIGIPAK ALBUM FISIK ”SEJAK TAK LAGI BERSAMA” KARYA GUNSALEH BERBASIS AUGMENTED REALITY - Rasi, Valentina; Bakti, Amar Ma'ruf Stya; Pramudya, Bintang (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2025)
The advancement of technology today has driven a significant transformation in the music industry, particularly for independent musicians. One of the challenges faced is the declining interest in physical albums due to the dominance of streaming platforms. This final project aims to create an innovative visual solution by designing a physical album integrated with Augmented Reality (AR), focusing on the album "Sejak Tak Lagi Bersama" by Gunsaleh, an indie musician from Malang. This approach not only serves as a visual communication strategy but also enhances audience engagement through interactive experiences. The design process employs a qualitative method, including literature studies, interviews, and visual observations. The visual concept utilizes the cactus as a representation of emotional resilience reflected in the songs’ narratives, applied through illustrations, layout, color schemes, and interactive elements. The album consists of eight panels, each measuring 15 x 15 cm, which can be scanned using a supporting application to activate AR content, adding both aesthetic and functional value. The main output of this project is an interactive physical album, accompanied by supporting media such as a display box, NFC keychain, journal, and other merchandise. The result is expected to serve as a reference for the development of technology-based visual design for independent musicians in Indonesia, and to offer a new alternative for experiencing physical music in the current era.